Factors Influencing Nonrenewal of Health Insurance Membership in Ejisu-Juaben Municipality of Ashanti Region, Ghana - Kwawukume Mawumenyo Aku; Kofi Akohene Mensah; Peter Twum; Peter Agyei-Baffour; Daniel Opoku; Joseph Kwasi Brenyah (Hindawi Limited, 2021)
Background. In the quest to prevent households from making catastrophic expenditures at the point of seeking healthcare, the government of Ghana introduced the National Health Insurance in 2003. However, people are reluctant to renew their membership. This study was, therefore, conducted to identify factors influencing the nonrenewal of National Health Insurance membership in the Ejisu-Juaben Municipality. Methods. A cross-sectional study was conducted among 427 respondents in the Ejisu-Juaben Municipality to ascertain factors influencing the nonrenewal of health insurance membership status. Data were entered and analyzed using Stata version 14. Univariate and multivariate analyses were performed to determine sociodemographic factors, household factors, and systemic factors influencing the nonrenewal of health insurance status. Statistical significance for all testing was set as p≤0.05. Results. Sociodemographic factors such as gender (AOR = 0.531; CI = 0.287-0.985) and educational level (AOR = 5.268; CI = 1.130-24.551)) were associated with the nonrenewal of health insurance membership. Income levels in Ghana Cedis were 500-1000 (AOR = 0.216; CI = 0.075-0.617) and 1001-2000 (AOR = 0.085; CI = 0.019-0.383). Systemic decision on factors such as clients' satisfaction (AOR = 0.149; CI = 0.035-0.640), making copayment (AOR = 0.152; CI = 0,068-0.344), acquiring all prescribed drugs (AOR = 4.191; CI = 2.027-8.668), and awareness of mobile renewal (AOR = 3.139; CI = 1.462-6.739) was associated with nonrenewal of membership. Conclusions. The nonrenewal of health insurance membership was influenced by sociodemographic, household, and systemic factors. Therefore, the Municipal Health Directorate and the National Health Insurance Authority have to work on these factors to reach the target of 100% active coverage in the municipality.